Seasonal Variation of Congenital Diaphragmatic Hernia: A Review of the Literature and Database Report from the United States and Canada - Doktor, Fabian; Antounians, Lina; Miller, Jason; Harb, Maria; Meats, Tracy; Bercovitch, Rachel; Ireland, Dawn; Zani, Augusto (European Journal of Pediatric Surgery, 2022)
Introduction The etiology of congenital diaphragmatic hernia (CDH) remains unknown and only 10 to 30% of patients have a genetic cause. Seasonal variation is known to contribute to the development of some congenital anomalies. Our aim was to investigate whether CDH births have seasonal variation.Materials and Methods A literature review was conducted for CDH and seasonality. Moreover, data from the CDH International Patient Registry Database were collected for infants with due dates between 2008 and 2014. Due dates were used to determine seasonal distribution of births. Birth rates per month in the United States and Canada were extracted from publicly available databases. Data were analyzed using analysis of variance and contingency tables.Results First, the literature review revealed 11 articles, of which 3 were eligible for inclusion. These studies reported conflicting results on seasonality of CDH. Second, we extracted due dates from the CDH International Patient Registry Database (1,259 patients) and found that there were fewer due dates in winter months (12.1 ± 4 patients/month) than in summer (16.7 ± 6 patients/month; p = 0.011) and fall months (16.3 ± 5 patients/month; p = 0.022). Although this trend was similar to that of all births in the United States and Canada, a lower incidence was observed in winter for CDH infants (20.2%) than for the general population (24.1%, p = 0.0012). CDH survival rate did not vary by season.Conclusion This study provides evidence for a seasonal variation of CDH births. No causative link was established between CDH development and seasonality. Population-based studies with a focus on exposome data are needed to explain seasonal variation in CDH.
Keywords: congenital diaphragmatic hernia; seasonality; survival; viral infection